1985
DOI: 10.1038/315768a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression of the gene encoding human erythroid-potentiating activity

Abstract: Erythropoietin is the primary physiological regulator of erythropoiesis; however, in vitro studies have identified another class of mediators which appear to be important in stimulating erythroid progenitors. These factors have generally been referred to as burst-promoting activities (BPA), because they stimulate the growth of early erythroid progenitors referred to as burst-forming units-erythroid (BFU-E) which give rise to colonies of up to thousands of haemoglobinized cells. We recently reported purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
0
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(127 citation statements)
references
References 20 publications
5
120
0
2
Order By: Relevance
“…Alternatively, since TIMP-1 preferentially binds the pro-enzyme form of MMP-9, upregulation of this inhibitor in GBM may reflect a specific regulatory mechanism that links these two functions, and could be seen as an attempt by the host to neutralize increased MMP-9 activity and thus slow invasion or angiogenesis. It is also possible that TIMP-1 may stimulate glioma proliferation directly in vivo since TIMP-1 has erythroid potentiating activity (EPA), and stimulates proliferation of numerous cell types (Gasson et al, 1985;Bertaux et al, 1991;Hayakawa et al, 1992Hayakawa et al, , 1994. Moreover, TIMP-1, but not TIMP-2 or the synthetic hydroxamate inhibitor BB-94, has been shown to confer resistance to apoptosis in Burkitt's lymphoma cells (Guedez et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, since TIMP-1 preferentially binds the pro-enzyme form of MMP-9, upregulation of this inhibitor in GBM may reflect a specific regulatory mechanism that links these two functions, and could be seen as an attempt by the host to neutralize increased MMP-9 activity and thus slow invasion or angiogenesis. It is also possible that TIMP-1 may stimulate glioma proliferation directly in vivo since TIMP-1 has erythroid potentiating activity (EPA), and stimulates proliferation of numerous cell types (Gasson et al, 1985;Bertaux et al, 1991;Hayakawa et al, 1992Hayakawa et al, , 1994. Moreover, TIMP-1, but not TIMP-2 or the synthetic hydroxamate inhibitor BB-94, has been shown to confer resistance to apoptosis in Burkitt's lymphoma cells (Guedez et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TIMP-1 stimulates the proliferation of erythroid precursors (Gasson et al, 1985), and both TIMP-1 and TIMP-2 can positively influence the proliferation of numerous cell types (Hayakawa et al 1992(Hayakawa et al , 1994Wingfield et al, 1999). Additionally, TIMP-2 inhibits in vitro proliferation of human microvascular endothelial cells stimulated with bFGF (Murphy et al, 1993), and TIMP-3 promotes apoptosis (Ahonen et al, 1998;Baker et al, 1998), possibly through stabilization of TNF alpha receptors (Smith et al, 1997).…”
mentioning
confidence: 99%
“…We identified an erythroid-potentiating activity (EPA) in the supernatant of the HTLV-II-transformed human T-lymphblast cell line (Me), and purified the 28 000 Da glycoprotein molecule to homogeneity [5,16]. Subsequent eDNA cloning demonstrated that EPA was identical to tissue inhibitor of metalloproteinases (TIMP, TIMP-1) [17,18], which can be isolated from a variety of human tissues and body fluids and which has been shown to inhibit the eollagenase family of enzymes [19][20][21]. The purified natural EPA and, subsequently, the recombinant EPA were shown to augment colony formation by human CFU-E, BFU-E and K-562 cells [16,17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent eDNA cloning demonstrated that EPA was identical to tissue inhibitor of metalloproteinases (TIMP, TIMP-1) [17,18], which can be isolated from a variety of human tissues and body fluids and which has been shown to inhibit the eollagenase family of enzymes [19][20][21]. The purified natural EPA and, subsequently, the recombinant EPA were shown to augment colony formation by human CFU-E, BFU-E and K-562 cells [16,17,22,23]. We were also able to demonstrate specific binding of radioiodinated recombinant EPA to the K-562 erythroleukemia cells [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation